The roles of mass media, word of mouth and subjective norm: a study of family takaful purchase intention in Gombak, Selangor / Faiznur Ishak - Ishak, Faiznur (2018)
The term Takaful is derived from the Arabic root word kafala which means responsibility, guarantee, amenability or suretyship. Hence, takaful means that joint guarantee or guaranteeing one another. Takaful is most referred as Islamic insurance as a result of the system that is based on the concept of social solidarity, cooperation and mutual indemnification of losses of members. There are two types Takaful products which has general takaful and family takaful which also known as life insurance from conventional perspective. According to the Insurance Services Malaysia Berhad (ISM), as cited in Etiqa Takaful Berhad (201 1) the Takaful industry in Malaysia has been experiencing steady growth and speedy changes over the last 5 years. However, in Malaysia, family Takaful market continues to be at a lower penetration level compare to other developed countries even though the Takaful industry continues to sustain strong performance. Proof has shown that the percentage of society covered by family Takaful contracts in Malaysia continues to be terribly low compared to conventional insurance. This study is to analyse the influence of mass media and word of mouth on subjective norm in addition as purchase intention specifically around Gombak that is in Selangor where a set of questionnaires will be distribute to the respondents that is selected using non-probability convenience sampling. The data will be analysing using regression analysis in order to determine the relationship between dependent variable which is Family takaful purchase intention and its independent variables which are Mass media, word of mouth and subjective norms.